Respuesta :
t^2-4t-32= 0, implies sqrtDelta = 6
so t = 2 - 6= -4, or t = 2+6= 8
so t^2-4t-32/t-8 = (t + 4) (t-8) / t-8 = t+4, it is the simplified form
so the answer is c. t + 4; t = 8
so t = 2 - 6= -4, or t = 2+6= 8
so t^2-4t-32/t-8 = (t + 4) (t-8) / t-8 = t+4, it is the simplified form
so the answer is c. t + 4; t = 8
Answer:
(C)t+4; t=8
Step-by-step explanation:
The given rational expression is:
[tex]\frac{t^2-4t-32}{t-8}[/tex]
Simplifying the above expression, we get
=[tex]\frac{t^2-8t+4t-32}{t-8}[/tex]
=[tex]\frac{t(t-8)+4(t-8)}{t-8}[/tex]
=[tex]\frac{(t+4)(t-8)}{(t-8)}[/tex]
=[tex]t+4[/tex]
which is the required simplified form of the given expression.
And the restrictions on the given expression is t=8, because when we substitute t=8 in the expression, it becomes infinite.
Thus, option C is correct.